Reading Single Words Aloud With Monocular Presentation: The Effect of Word Frequency - Serje Robidoux; Derek Besner (Frontiers in Communication, 2018)
Few phenomena in reading research are as ubiquitous as the observation (both within and across paradigms) that high frequency words are easier to process than lower frequency ones. Jainta et al. (2014, 2017) report an exception in that, when reading sentences with only one eye, the word frequency advantage disappeared. If this same pattern were seen in single word reading it would strongly challenge all current theoretical accounts of reading aloud currently on the table. The present experiment therefore explored whether this same pattern is evident when participants read aloud single words under monocular (vs. binocular) conditions. Bayesian analysis techniques reveal that, in contrast to the sentence reading results, a monocular condition does not modulate the word frequency effect when reading single words aloud. The present results thus point to a qualitative difference between word recognition processes seen in single word reading vs. those seen in eye tracking studies.